2009
DOI: 10.1200/jco.2008.16.3121
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Study of 1 Month Versus 1 Year of Adjuvant High-Dose Interferon Alfa-2b in Patients With Resected High-Risk Melanoma

Abstract: There were no significant differences in OS and RFS between the regimens of 1 month and 1 year of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 11 publications
2
50
1
2
Order By: Relevance
“…Patients in group B were treated with i.v. 15 Â 10 6 U/m 2 /d IFN-a2b (Intron; Merck & Co.) on days 1 to 5 each week for 4 weeks, and then followed by s.c. 9 Â 10 6 U IFN-a2b three times per week for 48 weeks, which has been confirmed by previous trial to be tolerable and may be the optimal dose intensity for Chinese patients and Europeans (25,26). Patients in group C were treated with per os 200 mg/m 2 /d temozolomide (Temodal or Temodar; Merck & Co.) on days 1 to 5 plus i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Patients in group B were treated with i.v. 15 Â 10 6 U/m 2 /d IFN-a2b (Intron; Merck & Co.) on days 1 to 5 each week for 4 weeks, and then followed by s.c. 9 Â 10 6 U IFN-a2b three times per week for 48 weeks, which has been confirmed by previous trial to be tolerable and may be the optimal dose intensity for Chinese patients and Europeans (25,26). Patients in group C were treated with per os 200 mg/m 2 /d temozolomide (Temodal or Temodar; Merck & Co.) on days 1 to 5 plus i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Patients in arm B had more grade 1 to grade 2 hepatotoxicity, nausea, vomiting, alopecia, and neurologic toxicity. Thus the study concluded that there is no difference between a one month and a one year treatment in terms of relapsed-free or overall survival (Pectasides et al, 2009). High dose interferon alpha-2b is however associated with toxic effects.…”
Section: Cytokines 221 Interferon Alpha-2bmentioning
confidence: 91%
“…In multivariable analysis, long-course hd-ifn was associated with improved survival (hazard ratio: 0.59; 95% cl: 0.38, 0.92). In another trial evaluating the effect of ifn duration on outcome, Pectasides et al 21 reported negative results, but their target dose was much less than the dose used in standard hd-ifn regimens. Although the supportive evidence is not robust, our observed association between pre-existing mental health care and early discontinuation of hd-ifn emphasizes, at minimum, the importance of optimizing the mental health care of patients who are to receive hd-ifn so as to ensure delivery of treatment per protocol.…”
Section: Discussionmentioning
confidence: 99%